Measuring relational memory in older and younger adults - Jennifer N. Sexton; Lillian Behm; Jill A. Rose; Connor J. Phipps; Meghan K. Ramirez; Abi M. Heller-Wight; Anna F. Wilhelm; Emma A. Armbruster; Carolyn E. Nagengast; David E. Warren (Frontiers in Cognition, 2025)
IntroductionChanges in cognitive abilities including memory accompany normal aging, and certain types of memory are particularly susceptible to age-related change. The ability to link aspects of an experience to form one cohesive memory, called relational memory, is essential to normal memory throughout the lifespan. Relational memory facilitates the binding of arbitrarily related stimuli and encompasses all manner of relations (spatial, associative, sequential). Prior work has studied differences in relational memory associated with aging but has investigated specific aspects of relational memory in a siloed fashion: earlier studies typically have not simultaneously assessed multiple aspects of relational memory in the same participants in the same paradigm.MethodsIn the current study, multiple aspects of relational memory were simultaneously compared between healthy younger adults (19–35 years, n = 40) and healthy older adults (65–77 years, n = 40).ResultsWe found that older adults had reduced memory performance relative to younger adults on each condition of the memory task (item condition, space condition, re-pair condition, and time condition), and there was a condition-by-age group interaction such that differences were greatest for the time and space conditions.DiscussionWe found age-related differences between young and older adults on a task simultaneously testing multiple types of relational memory with young adults performing better overall. Additionally, we observed condition-level interactions such that the age-related differences were greater for the time and space conditions than the re-pair condition. Together, these findings underscore the importance of measuring memory for all manner of relations using the same study format to achieve a thorough characterization of the complex nuances of relational memory performance across the lifespan.